2020
DOI: 10.3390/plants9101318
|View full text |Cite
|
Sign up to set email alerts
|

Hop Polyphenols in Relation to Verticillium Wilt Resistance and Their Antifungal Activity

Abstract: (1) Background: Verticillium wilt (VW) of hop is a devastating disease caused by the soil-borne fungi Verticillium nonalfalfae and Verticillium dahliae. As suggested by quantitative trait locus (QTL) mapping and RNA-Seq analyses, the underlying molecular mechanisms of resistance in hop are complex, consisting of preformed and induced defense responses, including the synthesis of various phenolic compounds. (2) Methods: We determined the total polyphenolic content at two phenological stages in roots and stems o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…For example, cinnamic acid is induced by beneficial Rhizobia bacteria in rice and is implicated in resistance to Rhizoctonia (Mishra et al, 2006 ). Another polyphenol called tyrosyl was shown to have very potent antifungal activity not only in plant diseases but also in human infections (Abdel-Rhman et al, 2020 ; Berne et al, 2020 ). Sinapinaldehyde or Sinapyl aldehyde is another class of antifungal compound produced naturally in plants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cinnamic acid is induced by beneficial Rhizobia bacteria in rice and is implicated in resistance to Rhizoctonia (Mishra et al, 2006 ). Another polyphenol called tyrosyl was shown to have very potent antifungal activity not only in plant diseases but also in human infections (Abdel-Rhman et al, 2020 ; Berne et al, 2020 ). Sinapinaldehyde or Sinapyl aldehyde is another class of antifungal compound produced naturally in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Plant phenolics originate from the phenylpropanoid and polyketide pathways, or a combination of both, and can directly inhibit the growth of pathogenic fungi . Phenolic acids were extracted from cotton plants infected with different V.…”
Section: Resultsmentioning
confidence: 99%
“…Plant phenolics originate from the phenylpropanoid and polyketide pathways, or a combination of both, and can directly inhibit the growth of pathogenic fungi. 27 Phenolic acids were extracted from cotton plants infected with different V. dahliae strains and detected via HPLC. The results indicated that the content of phenolic acids in the ΔVdOrlp-infected cotton roots were significantly lower than that in the V991-or VdOrlp OE -inoculated roots (Figure 6A).…”
Section: Deletion Of Vdorlp Reduces the Tolerance Of V Dahliae To Phe...mentioning
confidence: 99%
“…In particular, plants have promoted their defense mechanism to fight invading spoilage organisms ( Köhl, Kolnaar & Ravensberg, 2019 ). Some plant genes are RNA-seq responsible for defense against a plant root spoilage organism, Verticillium dahlia ( Berne et al, 2020 ). They produced a plant-based signal transduction pathway web, which was initiated to acknowledge elicitors with safety indication materials and Pathogen-Associated Molecular Patterns that observe microbes like those that essentially relate to the roots of the plant in their soil habitat.…”
Section: Various Associations Occurring Between Microorganisms and To...mentioning
confidence: 99%